Quantitative and Qualitative Analysis of Platelet GPIb and von Willebrand Factor in Liver Cirrhosis - Beer, J H; Clerici, N; Baillod, P; von Felten, A; Schlappritzi, E; Büchi, L (Thrombosis and Haemostasis, 1995)
Numerous abnormalities of plasmatic coagulation and platelet function may contribute to the bleeding in liver cirrhosis with a defective platelet-von Willebrand factor interaction being a potential mechanism. To analyze GPIb and von Willebrand factor in cirrhosis, we quantified the number of GPIb molecules on the platelet surface by flow cytometry, assessed the total (and indirectly the internal) pool of GPIb by ELISA and measured the circulating amount of glycocalicin in plasma as a measure of proteolytic activity and platelet turnover. Von Willebrand factor was characterized by ELISA, by its ristocetin-cofactor activity and by multimer analysis. Botrocetin-induced agglutination was used for functional analysis.The data from 8 well-characterized cirrhosis patients indicate that total GPIb is insignificantly increased to 46,000 ± 5,000 molecules/P (normal: 39,500 ± 2,000 [SEM]), surface-GPIb is normal with some variability and that the glycocalicin levels are 2-3 times higher than would be expected from the platelet count (= 100 ±5 × 109/1). Von Willebrand factor antigen levels and -activity were 400-500 % of normal with a 22% reduction of the high molecular weight multimers. A significant hyperagglutination response to botrocetin was observed with platelets from both patients and controls using patient plasma as a source of von Willebrand factor. In conclusion, a hyperresponsiveness rather than a defective platelet-von Willebrand factor interaction can be observed in cirrhosis which may compensate for other hemostatic problems and appears to be mediated primarily by increased levels of von Willebrand factor.